Anestesia raquídea versus sedoanalgesia para legrado uterino instrumental. - Cevallos Unda, Verónica del Carmen. (2015)
The present observational descriptive and comparative work was held in which their objectives are to compare both anesthetic techniques, as well as how to evaluate the hemodynamic change, to determinate the level of the analgesics, the results that we obtained will be compared in both patients that are under the spinal anesthesia as well as in patients under the sedoanalgesia “which is a is a combination of sedation and local anesthesia” during the anesthesia recovery period and to determinate the most frequently side effects in which they were presented at the moment of applying these techniques to women “ASA” 1 and 2 that were submitted to a sharp curettage. For it there was a total of 60 random patients included, 30 with the sedoanalgesia and 30 with the spinal anesthesia. The vital signs were also evaluated, recovery time, postoperative analgesia and the side effects. The results showed that there aren’t any statistically significant differences in terms of variations in vital signs, pain management or side effects, concluding that both methods are a great option for an anesthetic technique for patients that will be taken up to a sharp curettage, even though in the group of the technique with the spinal anesthesia the recovery time was a bit longer there was a better pain management and there was no need of any other analgesic during the postoperative step. Key words: Instrumental sharp curettage, sedation, spinal anesthesia